Selective Recognition of Ammonium over Potassium Ion with Acyclic Receptor Molecules Bearing 3,4,5-Trialkylpyrazolyl Groups - Fuhrmann, Felix; Seichter, Wilhelm; Mazik, Monika (Organic Materials, 2022)
Among the 1,3,5-trisubstituted 2,4,6-triethylbenzenes bearing pyrazolyl groups, the compounds with 3,5-dimethylpyrazolyl moieties were found to be effective receptors for ammonium ions (NH4+). The current study investigated the extent to which the incorporation of an additional alkyl group in the 4-position of the pyrazole ring affects the binding properties of the new compounds. 1H NMR spectroscopic titrations and investigations using isothermal titration calorimetry revealed that this small structural variation leads to a significant increase in the binding strength towards NH4+ and also improves the binding preference for NH4+ over K+. In addition to the studies in solution, crystalline complexes of the new triethyl- and trimethylbenzene derivatives, bearing 3,4,5-trialkylpyrazolyl groups, with NH4+PF6− were obtained and analyzed in detail. It is noteworthy that two of the crystal structures discussed in this work are characterized by the presence of two types of ammonium complexes. Studies focusing on the development of new artificial ammonium receptors are motivated, among other things, by the need for more selective ammonium sensors than those based on the natural ionophore nonactin.
Keywords: molecular recognition; ammonium receptors; selectivity; structure–binding activity relationships